Propagation technique of Kacip Fatimah (Labisia pumila) under glasshouse condition using mist irrigation - Mohd Ghazali, Nur Harapan; Jaafar, Hawa Z. E.; Ibrahim, Mohd Hafiz; Megat Wahab, Puteri Edaroyati; Awang, Nafisah; Mohd Nor, Nik Mohamad Adnan (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Labisia pumila, commonly known as Kacip Fatimah (KF), has very high economic potential as demand for alternative medicine in the form of herbal product becomes important worldwide. Currently, KF is heavily collected from forest floor increasing from 30,000 (2010) to >100,000 (2012) plants to accommodate high demand from herbal industry players; this may cause species extinction if no alternative measure to produce the raw material is attempted. Furthermore, quality, authenticity, and consistency of supply from collection are always questionable affecting the overall development prospect of national herbal industry. Hence, propagation and domestication of KF becomes very pertinent to ensure continuous quality supply. Our work on the propagation of KF two most popular varieties (Alata and Pumila) using mist irrigation technique under glasshouse condition showed the possibility of mass producing new plants of authentic KF through leaf cutting. This propagation technique can also ensure a sustainable production of 9- to 15-folds more new plants promising an estimated gross income of RM1.35M to RM2.25M per annum, beside supplying the pharmaceutical company with quality and authentic raw material and conserving the biodiversity. The transfer of this knowledge involved visits, discussion, talks, seminar and trainings of nursery workers to acquire skill and understanding of work procedure.